2009
DOI: 10.1111/j.1476-5381.2009.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

The histamine H4 receptor is functionally expressed on neurons in the mammalian CNS

Abstract: Background and purpose:The histamine H4 receptor is the most recently identified of the G protein-coupled histamine receptor family and binds several neuroactive drugs, including amitriptyline and clozapine. So far, H4 receptors have been found only on haematopoietic cells, highlighting its importance in inflammatory conditions. Here we investigated the possibility that H4 receptors may be expressed in both the human and mouse CNS. Methods: Immunological and pharmacological studies were performed using a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
177
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(183 citation statements)
references
References 47 publications
4
177
0
2
Order By: Relevance
“…Conventional immunohistochemical procedures were employed as described previously [30,31] AQP3, -NKCC1, -TNAP and -THP (4 µg/ml) at 4°C, followed by a three-layer streptavidin-biotin-peroxidase complex staining method (Vectastain ABC Elite kit and 3',3-diaminobenzadine tetrahydrochloride, DAB; Vector Laboratories, Inc.). Tissue was also screened in the absence of primary antibody.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Conventional immunohistochemical procedures were employed as described previously [30,31] AQP3, -NKCC1, -TNAP and -THP (4 µg/ml) at 4°C, followed by a three-layer streptavidin-biotin-peroxidase complex staining method (Vectastain ABC Elite kit and 3',3-diaminobenzadine tetrahydrochloride, DAB; Vector Laboratories, Inc.). Tissue was also screened in the absence of primary antibody.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…H4R expression has been reported in peripheral nerves and in the neurons of the submucous plexus (Nakaya et al, 2004;Breunig et al, 2007). More recently it has been observed the presence of H4R receptors in numerous areas of the central nervous system (CNS), such as hippocampus, thalamus, amygdala, cortex, striatum and spinal cord (Strakhova et al, 2009;Connelly et al, 2009). Electrophysiological studies showed that H4R directly hyperpolarized cortical neurons (Connelly et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…More recently it has been observed the presence of H4R receptors in numerous areas of the central nervous system (CNS), such as hippocampus, thalamus, amygdala, cortex, striatum and spinal cord (Strakhova et al, 2009;Connelly et al, 2009). Electrophysiological studies showed that H4R directly hyperpolarized cortical neurons (Connelly et al, 2009). More recent studies on the potential roles for H4R in the human brain from its predicted functional interactions in the human proteome suggested the participation of H4R in circadian cycle modulation, neuronal firing inhibition and, in cooperation with H3R, in thyroid function and appetite coordination (Moya-Garcia et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Histamine is synthesized from l-histidine by the enzyme histidine decarboxylase (HDC) and its effects are mediated by four histamine receptors in the brain: the histamine H 1 , H 2 , H 3 and H 4 receptors (H 1 R, H 2 R, H 3 R and H 4 R). H 1 R and H 2 R are mainly postsynaptic excitatory receptors whereas H 3 R and H 4 R are inhibitory receptors coupled to G i/o proteins [7,8]. H 3 R were originally described as presynaptic autoreceptors located on histaminergic axons and their activation inhibits the release and synthesis of histamine [9].…”
Section: Introductionmentioning
confidence: 99%